During vegetative growth period, sugarcane required a lot of water but decreasing afterward and minimum at ripening period. Sugarcane water requirement was calculated by radiation method and USDA (1969) method was used to determinate effective rainfall. Average of monthly actual evapotranspiration (ETa) was calculated by the available soil water index. The total of water requirement of sugarcane (1-12 month) was around 37.38 mmlmonth to 143.22 mmlmonth. The highest water requirement was found at - Herlika Asriasuri; Nora H Pandjaitan (Jurnal Keteknikan Pertanian, 1998)
During vegetative growth period, sugarcane required a lot of water but decreasing afterward and minimum at ripening period. Sugarcane water requirement was calculated by radiation method and USDA (1969) method was used to determinate effective rainfall. Average of monthly actual evapotranspiration (ETa) was calculated by the available soil water index. The total of water requirement of sugarcane (1-12 month) was around 37.38 mmlmonth to 143.22 mmlmonth. The highest water requirement was found at age of 4 to 9 month, while the lowest was in the ripening period. Accordingly drip irrigation should be operated at maximum water use of about 3.96 mm/day, or by sprinkle irrigation not less than 118.70 mm/mounth.